Penentuan Kualitas Akademik Mahasiswa Dengan Logika Fuzzy pada STMIK Mikroskil - Andri Andri; Paulus Paulus; Hanes Hanes (Fakultas Informatika, 2019)
With the mission of improving the quality of human resources in information and communication technology, STMIK Mikroskil should monitor the academic quality of the students regularly so that graduate GPA is not low and the number of students who do not graduate on time increasingly minimal. The problem faced is the lack of standardized criteria among study program in the determination of the students' academic quality, causing unevenness and subjective tendencies. The study program managers also are not easy to get this information.This study is to propose a model and an application to determine the level of academic quality of students from various inputs, namely the percentage of attendance, failed mid / end of semester grade, GPA, the frequency of semester grade point decrease using fuzzy logic. Fuzzy logic chosen because this method is suitable for handling subjective criteria. Fuzzy inference system method is mamdani. Defuzzification method is weighted average. The output is academic quality and type of action.The calculation result from the application program has been in accordance with MS Excel. Proposed system is expected to provide objective information about the academic quality of the students and can facilitate study program managers to control low academic quality.